Social media influencing in the city of likes : Dubai and the postdigital condition - Hurley, Zoe (Emerald Publishing Limited, 2023)
Dubai's audacious architecture and photographic locations attract social media 'influencers' from around the world. How has Dubai, once a small fishing village on the edge of a desert, morphed into a hyper-modern backdrop for this global phenomenon? How can we understand these interactions as our relationships with digital technologies undergo radical change? This timely research-based study reveals how micro-celebrities and Dubai's visible economies influence the evolution of the Emirate. Taking a cutting edge post-digital approach, underpinned by cultural studies and social media theory, Social Media Influencing in The City of Likes presents a series of unique case studies and demonstrates how Dubai is considered not only an illusion of unlimited indulgence but also a city dependent on the emerging infrastructure of visible economies, visual attractions, and 'Instagrammable' locations. Evaluating the cases of multiple influencers, from local to transnational content creators, Hurley reveals how residents, non-citizens and migrant workers surviving as influencers in the city of 'likes.' Providing a much-needed de-Westernising perspectives of Dubai's social media influencing industry within the broader context of global platform capitalism, Social Media Influencing in The City of Likes offers an important contribution to the field of social media through illustrating visible economies in a city circuited by social media influencing.
Keywords: Social media and society -- United Arab Emirates -- Dubai.; Internet personalities -- United Arab Emirates -- Dubai.; Internet marketing -- Social aspects -- United Arab Emirates -- Dubai.; Dubai (United Arab Emirates) -- Social life and customs.; Social Science -- Media Studies.; Social groups.; elektronické knihy; electronic books